PENYULUHAN OPTIMALISASI LAHAN PEKARANGAN PERTANIAN SEBAGAI UPAYA PENURUNAN STUNTING PADA KELOMPOK TANI MILENIAL DI DESA ADAT CITOREK SABRANG KABUPATEN LEBAK - Hijrah Wicaksana, Harits (Jurnal Abdimas Bina Bangsa, 2025)
However, food instability and nutrient consumption below the required level can occur in some areas, which leads to stunted growth. The sustainable food yard utilization program for stunting using vertical bioconversion technology can stop this. Encourage the community, especially millennial farmers, to use their home yards (surrounding environment) to meet their nutritional needs independently. According to the activity results, all participating farmers - 100% of them - showed interest in utilizing vertical bioconversion technology, especially when using vertical cultivation techniques to utilize yards as agricultural land. However, only 80% of participating farmers showed interest in bioconversion, which uses maggot cultivation to produce animal feed and compost. This is because the fermentation of organic waste is a source of food for maggots, and farmers need to learn more about how to produce it. To meet their nutritional needs, farmers are also asked to plant staple crops that have economic value such as pak choy, chilies, and spinach. 40% said they were very happy with the training, while 60% said they were satisfied